Positron emission tomography in patients with psychogenic non-epileptic seizures - McGonigal A; Arthuis M; Micoulaud J; Bartolomei F; Guedj E (Neuropsychiatric Disease and Treatment)
Aileen McGonigal,1–3 Marie Arthuis,3 Jean-Arthur Micoulaud-Franchi,4,5 Fabrice Bartolomei,1–3 Eric Guedj6–8 1Institut de Neurosciences des Systèmes, INSERM UMR 1106, Marseille, France; 2Aix Marseille University, Faculty of Medicine, Marseille, France; 3Clinical Neurophysiology Department, Timone Hospital, Marseille, France; 4Department of Functional Investigation of the Nervous System, Sleep Clinic, Bordeaux University Hospital, Bordeaux, France; 5USR CNRS 3413, University of Bordeaux, France; 6Biophysics and Nuclear Medicine Department, Timone Hospital, Marseille, France; 7Aix-Marseille University, CERIMED, Marseille, France; 8Aix-Marseille University, CNRS, UMR7289, INT, Marseille, FranceWe have read with interest the recent review entitled “Uncovering the etiology of conversion disorder: insights from functional neuroimaging” by Maryam Ejareh dar and Richard AA Kanaan,1 published in Neuropsychiatric Disease and Treatment. Our paper on resting state brain metabolism measured by positron emission tomography (PET) was included and discussed.2 We were most surprised to see that the authors of the review seem to have misunderstood the findings of our study, which concerned patients with psychogenic non-epileptic seizures (PNES). The authors state that the 16 patients included in our study “were later found to have PNES with comorbid epilepsy”. This is incorrect, since our study included only patients with PNES in whom comorbid epilepsy was excluded. This crucial point is indeed detailed in the Methods section of our article and clearly stated in the abstract: “in all patients, the diagnosis was subsequently confirmed to be PNES with no coexisting epilepsy.” It is thus on the basis of incorrect understanding of our results that Drs Ejareh dar and Kanaan discuss the possible significance of hypometabolism in the anterior cingulate region described in our paper, and erroneously suggest that interpretation of PET findings is complicated by coexistent epilepsy, which was not in fact the case.Read the original article.